(untitled) (Research, Society and Development, 2022)
Introduction: Chronic non-communicable diseases are the main causes of morbidity and mortality today, among them, Arterial Hypertension (SAH) and Type 2 Diabetes Mellitus (T2DM), which are responsible for a variety of systemic complications. Both conditions share, in their pathophysiology, the state of oxidative stress, justifying the possible use of antioxidant components, such as flavonoids. Objectives: To characterize and describe the therapeutic potential of the main medicinal plants of popular use, rich in flavonoid-type antioxidant constituents, in the treatment of hypertension and diabetes. Methodology: An integrative literature review study, developed from a survey in PubMed, MEDLINE and LILACS databases. Results: From the survey, the following plants used for hypertension stood out: Hibiscus sabdariffa, Allium sativum L., Phyllathus amarus, Ginkgo biloba and Matricaria chamomilla. As for diabetes, the following stand out: Syzygium cumini L., Caesalpinia sappan, Andrographis paniculata and Curcuma longa L. Conclusion: The results showed that the use of medicinal plants rich in flavonoids can serve as an important ally in the prevention, control and treatment. of SAH and T2DM, acting mainly against the state of oxidative stress, a common pathophysiological mechanism in both diseases, and thus preventing the occurrence of complications resulting from this state.